Computational procedure for determining the limiting values of the loading parameters of mechanical systems - Struzhanov, Valeriy Vladimirovich; Burmasheva, Natalia Vladimirovna (Computational Continuum Mechanics, 2011)
A technique for calculating the limiting values of the loading parameters of mechanical systems with a finite number of elements is presented. The technique is based on the approximate method of constructing the separatrix of the potential functions of such systems. To illustrate the validity of the proposed approach, the problem of determining limiting loads applied to the rod system, which is used for triaxial stretching of an elementary cube made of nonlinear material, is solved.
Keywords: gradient system; potential function; separatrix; nonconvex potential; maximum loads